Synthesis and spectroscopic characterization of new heteroleptic ruthenium(II) complexes incorporating 2-(2′-pyridyl) quinoxaline and 4-carboxy-2-(2′-pyridyl)quinoline - Philippopoulos, A.; P. Falaras; Chatzivasiloglou, E.; Igglessi-Markopoulou, O.; V. Likodimos; Konti, G.-C. (Journal of Coordination Chemistry, 2012)
Starting from cis-[Ru(dcbpyH 2) 2Cl 2] (1), two new heteroleptic ruthenium(II) complexes, [Ru(dcbpyH 2) 2(L 1)](NO 3) 2 (L 1=2- (2′-pyridyl)quinoxaline (2), and [Ru(dcbpyH 2) 2(L 2)](NO 3) 2 (L 2=4- carboxy-2-(2′-pyridyl)quinoline (4); dcbpyH 2=2,2′- bipyridine-4,4′-dicarboxylic acid), were synthesized and spectroscopically characterized. During the preparation of 2 and 4, the homoleptic [Ru(dcbpyH 2) 3]Cl 2 complex (3) was isolated as a side product. Characterization includes IR and Raman spectroscopy, UV-Vis, multinuclear NMR spectroscopy, elemental, and ESI-mass spectrometric analyses. © 2012 Taylor and Francis.